HUMAN RESOURCE MANAGEMENT IN A DENTAL CLINIC: A CASE STUDY OF DENTAL CARE SENGON JOMBANG - Wahyuni, Indah (INSTITUT TEKNOLOGI DAN BISNIS PGRI DEWANTARA JOMBANG, 2025)
This study aims to analyze human resource management practices at Dental Care Sengon Jombang, with a particular focus on human resource planning, development, and maintenance. The study employed a qualitative approach using a case study design. Data were collected through in-depth interviews, observation, and documentation involving individuals directly engaged in the clinic’s operations. The findings indicate that human resource management at the clinic has been implemented through three main functions. Workforce planning is carried out flexibly in accordance with service needs, human resource development is conducted through training and direct workplace learning, and human resource maintenance is reflected in open, flexible, and family-oriented working relationships. These findings suggest that human resource management practices at the clinic have supported operational continuity and service quality, although they remain adaptive in nature and have not yet been fully formalized. This study underscores the importance of strengthening more structured human resource management systems in small-scale healthcare facilities